2022
DOI: 10.1126/sciadv.abq6376
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of integrons in Archaea: Platforms for cross-domain gene transfer

Abstract: Horizontal gene transfer between different domains of life is increasingly being recognized as an important evolutionary driver, with the potential to increase the pace of biochemical innovation and environmental adaptation. However, the mechanisms underlying the recruitment of exogenous genes from foreign domains are mostly unknown. Integrons are a family of genetic elements that facilitate this process within Bacteria. However, they have not been reported outside Bacteria, and thus their potential role in cr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 83 publications
1
13
0
Order By: Relevance
“…Two adjacent attC sites were selected from each phage for their ability to integrate into attI1 ( Table 2 ). Using a previously described conjugation-based attC x attI1 recombination assay ( Bouvier et al, 2005 ; Nivina et al, 2020 ; Ghaly et al, 2022b ), we showed that gene cassette insertion can take place following the transfer of single-stranded suicide vector DNA with phage-borne attC sites (bottom strands) into an intI1 -expressing E . coli recipient strain that also harbours an attI1 site ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two adjacent attC sites were selected from each phage for their ability to integrate into attI1 ( Table 2 ). Using a previously described conjugation-based attC x attI1 recombination assay ( Bouvier et al, 2005 ; Nivina et al, 2020 ; Ghaly et al, 2022b ), we showed that gene cassette insertion can take place following the transfer of single-stranded suicide vector DNA with phage-borne attC sites (bottom strands) into an intI1 -expressing E . coli recipient strain that also harbours an attI1 site ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…The attC donor strains were then isolated on LB agar selective media containing kanamycin (Km) and diaminopimelic acid (DAP). To generate attC donor plasmids that deliver the top strands of the respective attC sites, the same pairs of overlapping long primers were annealed and ligated to the Xba I/ Bam HI restriction sites of the pJP5603rev vector with its oriT in an inverted orientation relative to that of the pJP5603 parental vector ( Ghaly et al, 2022b ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obligatory association of Psyn with co-cultured bacteria might have favored the gene exchanges, possibly influencing microbial population structure under natural conditions 46 . Several different archaeal molecular mechanisms facilitating cross-domain DNA transfer, including integrons 47 ,have been described 48 , thus providing plausible means for HGT between Bacteria and Asgard. Finally, frequent HGTs between Psyn and different bacterial species might partially explain the apparent chimeric profiles of Asgard genomes 49 , which seemingly result from the frequent mixing of ancestral archaeal genes with laterally inherited bacterial ones.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the true extent of integron distribution is likely much broader, with recent discoveries showing that integrons also occur in archaea. This suggests that they are evolutionarily ancient elements that could play a role in cross‐domain gene transfer (Ghaly, Tetu, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%